Palm stearin as low trans hard stock for margarine - Miskandar Mat Sahri,; Nor Aini Idris, (Universiti Kebangsaan Malaysia, 2010)
Formulation models of brick margarine prepared from the interesterified of a fully hydrogenated palm stearin (POS) and palm kernel oil (PKO), POS of low iodine values and sunflower oil (SFO) were characterised, physically and chemically. Formulations with low trans fatty acid content were used in the margarine preparation and the products were evaluated for 25 days at storage temperatures of 5, 10 and 15oC. The study had shown that formulations of POS in the form of simple blend with PKO and SFO (sample 900), blend of interesterified fully hydrogenated POS with PKO and SFO (sample 905) and simple blend of fully hydrogenated POS with PKO and SFO (sample 904) could achieve similar fatty acid composition, but not SFC profile. The results showed that POS was not only a suitable hard stock in trans-free brick margarine formulations but provided functional property in product texture. The formulations, with saturated fatty acid content < 36% and < 1% trans fatty acid had produced brick margarine with the desired spreadability at refrigerator temperature (5-15oC).